Neural computation, neural devices, and neural prosthesis - Yang, Zhi (Springer New York, 2014)
In the past decades, interdisciplinary investigations overlapping biology, medicine, information science, and engineering have formed a very exciting and active field that attracts scientists, medical doctors, and engineers with knowledge in different domains. A few examples of such investigations include neural prosthetic implants that aim to improve the quality of life for patients suffering from neurologic disease and injury; brain machine interfaces that sense, analyze, and translate electrical signals from the brain to build closed-loop, biofeedback systems; and fundamental studies of intelligence, cognitive functions, and psychological behaviors correlated to their neurological basis.   Although this interdisciplinary area is still in its infancy, it can potentially create some of the most significant impact: treating diseases that are considered untreatable, interpretation and communication of neuron ensembles, or even a revolutionary perception and understanding of life different from philosophical or immaterial approaches. Fortunately, several academic societies recognize the value and impact of this growing field, firmly supporting related research. Such support will drive a booming future in the next twenty or thirty years. Research in this area is frequently project-driven, and the generated knowledge has been scattered in different fields of neuroscience, computation, material and technology, circuits and system, clinical reports, and psychology-the scope considerably across the boundary of traditionally defined disciplines. Neural Computation, Neural Devices, and Neural Prosthesis is intended to assemble such knowledge, from there suggesting a systematic approach guiding future educational and research activities. The targeted audience includes both students and researchers.